Selective Hydrolysis of Ovalbumin Promoted by Hf(IV)-Substituted Wells-Dawson-Type Polyoxometalate - Anyushin, Alexander V.; Sap, Annelies; Quanten, Thomas; Proost, Paul; Parac-Vogt, Tatjana N. (Frontiers in Chemistry, 2018)
The reactivity and selectivity of Wells-Dawson type polyoxometalate (POM), K16[Hf(α2-P2W17O61)2]·19H2O (Hf1-WD2), have been examined with respect to the hydrolysis of ovalbumin (OVA), a storage protein consisting of 385 amino acids. The exact cleavage sites have been determined by Edman degradation experiments, which indicated that Hf1-WD2 POM selectively cleaved OVA at eight peptide bonds: Phe13-Asp14, Arg85-Asp86, Asn95-Asp96, Ala139-Asp140, Ser148-Trp149, Ala361-Asp362, Asp362-His363, and Pro364-Phe365. A combination of spectroscopic methods including 31P NMR, Circular Dichroism (CD), and Tryptophan (Trp) fluorescence spectroscopy were employed to gain better understanding on the observed selective cleavage and the underlying hydrolytic mechanism. 31P NMR spectra have shown that signals corresponding to Hf1-WD2 gradually broaden upon addition of OVA and completely disappear when the POM-protein molar ratio becomes 1:1, indicating formation of a large POM/protein complex. CD demonstrated that interactions of Hf1-WD2 with OVA in the solution do not result in protein unfolding or denaturation even upon adding an excess of POM. Trp fluorescence spectroscopy measurements revealed that the interaction of Hf1-WD2 with OVA (Kq = 1.1×105 M-1) is both quantitatively and qualitatively slightly weaker than the interaction of isostructural Zr-containing Wells-Dawson POM (Zr1-WD2) with human serum albumin (Kq = 5.1×105 M-1).